Method of construction of membership functions information parameter dynamic modes road rollers - Вікторова, Олена Вікторівна (Eastern-European Journal of Enterprise Technologies, 2011)
The article is studied influence of different membership functions on quality of decision-making. Having applied on result of experimental researches of the dynamical load was developed the method of classification the mode of road machine on the basis of fuzzy logic